A Review of Public Housing Delivery System in Ogun State, Nigeria - Adebimpe, Orekan, Atinuke (International Journal of Property Sciences (E-ISSN: 2229-8568), 2019)
The importance of housing in Nigeria and the various housing strategies formulated by the Ogun state government in solving housing problems and efforts that have been made to-date has been acknowledged. Despite those efforts, it seems that much has not been achieved in terms of the availability of affordable housing. This paper provides a review of the housing programmes as well as public housing delivery in Nigeria with a further examination of the public housing delivery in Ogun State. In order to achieve this aim, a review of the relevant literature pertaining to public housing is made. A primary data gathering exercise is made with the senior officials at the Ogun State Housing Corporation (OSHC) to uncover the challenges as well as the strategies in place for the provision of affordable housing in Ogun State. The data was then supported with data from housing files obtained at the agency. It was revealed that OSHC has four (4) basic public estates in which allocation is made to the public. It was also noted in this study that (OSHC) is tilted to profit-making instead of social welfarism. This has made housing less affordable to the low and medium income earners.